2018
DOI: 10.1093/ndt/gfy302
|View full text |Cite
|
Sign up to set email alerts
|

Is there long-term value of pathology scoring in immunoglobulin A nephropathy? A validation study of the Oxford Classification for IgA Nephropathy (VALIGA) update

Abstract: Background It is unknown whether renal pathology lesions in immunoglobulin A nephropathy (IgAN) correlate with renal outcomes over decades of follow-up. Methods In 1130 patients of the original Validation Study of the Oxford Classification for IgA Nephropathy (VALIGA) cohort, we studied the relationship between the MEST score (mesangial hypercellularity, M; endocapillary hypercellularity, E; segmental glomerulosclerosis, S; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 30 publications
2
51
0
3
Order By: Relevance
“…The MEST‐C components that showed significant association with the prognosis of native IgAN varied in previous studies, and the implication of the Oxford classification has remained debatable . A meta‐analysis and a recent validation study showed that the M, S, T, and C scores were important predictive parameters for the prognosis of native kidney IgAN even after the consideration of bias from immunosuppressive treatment . Furthermore, the T score was most prominently associated with kidney function loss in native IgAN, suggesting that final tubular injury may be the chronic consequence of intraglomerular disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…The MEST‐C components that showed significant association with the prognosis of native IgAN varied in previous studies, and the implication of the Oxford classification has remained debatable . A meta‐analysis and a recent validation study showed that the M, S, T, and C scores were important predictive parameters for the prognosis of native kidney IgAN even after the consideration of bias from immunosuppressive treatment . Furthermore, the T score was most prominently associated with kidney function loss in native IgAN, suggesting that final tubular injury may be the chronic consequence of intraglomerular disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, tubular atrophy/interstitial fibrosis in the participants with low levels of hemoglobin was severer than that in the participants with high levels of hemoglobin, and hemoglobin levels correlated negatively to the grade of tubular atrophy/interstitial fibrosis (male: r = −0.15, p < 0.001; female: r = −0.12, p < 0.001). Tubular atrophy/interstitial fibrosis has been demonstrated to be associated with progression of IgAN [37][38][39]. Therefore, low levels of hemoglobin may indicate worse tubular atrophy/interstitial fibrosis that was associated with IgAN progression.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term outcome of pediatric IgAN in the VALIGA cohort was investigated in a recent study updating the database and prolonging the follow-up from 4.7 to 7.0 years [13]. At 20 years from renal biopsy, 20% of the 174 children developed 50% eGFR loss or ESRD.…”
Section: Clinical Features Of Children and Young Subjects With Igan Imentioning
confidence: 99%
“…The Japanese reports on an increase in T lesions in children in whom the decision for renal biopsy was delayed or when CS were not used [25, 26] have further stressed the attitude for Europe to treat progressive IgAN in children with aggressive therapy [18, 27, 28]. In Europe, the results of the long-term follow-up of the VALIGA study [13] clearly indicated that when T lesions develop, the disease enters a relentless phase of progression, and that M1, S1, and also C lesions in untreated cases can have an impact on disease outcome decades later in children as well as in adults.…”
Section: Treatment Of Pediatric Igan In Europementioning
confidence: 99%